Performance of advance opium poppy (Papaver somniferum) selections for latex, morphine and seed yields - Pareek, S K; Srivastava, V K; Maheshwari, M L; Gupta, R (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during winter season of 1987-88 to 1990-91 to evaluate the performance of advance opium poppy (Papaver somniferum L.) germplasm for latex, morphine and seed yields. The multi-locational testing was done at 5 places, viz New Delhi, Lucknow, Faizabad, Mandsaur and Udaipur. Three genotypes :UO 285', 'NOP 4' and 'NBRI 3' were found promising, and may be grown in different opium-growing regions in India. Two selections 'NC 57913' and 'NC 57955' from Kota genepool excelled the recommended cultivars 'IC 42' and' JA 16' in latex and seed yield at different locations and different years.